Phylogenetic Diversity, Antibiotic Resistance, and Virulence of Escherichia coli Strains from Urinary Tract Infections in Algeria - Anfal Kara; Chiara Massaro; Giovanni M. Giammanco; Rosa Alduina; Naouel Boussoualim (MDPI AG, 2024)
Urinary tract infections (UTIs) caused by Escherichia coli represent a significant public health concern due to the high virulence and antimicrobial resistance exhibited by these pathogens. This study aimed to analyze the phylogenetic diversity and antibiotic resistance profiles of Uropathogenic E. coli (UPEC) strains isolated from UTI patients in Algeria, focusing on virulence factors such as extended β-lactamase (ESBL) production, biofilm formation, and hemolytic activity. Phylogenetic grouping of 86 clinical imipenem resistant E. coli isolates showed the prevalence of group B2 (48.9%), followed by groups E (22.1%), unknown (12.8%), A (8.1%), and B1 (4.7%), and Clade I, D, Clade I, or Clade II (1.2%). The highest resistance rates were observed towards amoxicillin (86.04%), ticarcillin (82.55%), piperacillin (73.25%), nitrofurantoin (84.88%), and trimethoprim-sulfamethoxazole (51.16%). Notably, 69.8% of UPEC strains were multidrug-resistant (MDR) and 23.2% were extensively drug-resistant (XDR). Additionally, 48.9%, 42%, and 71% of strains demonstrated ESBL production, hemolytic activity, and weak biofilm production, respectively. Continuous monitoring and characterization of UPEC strains are essential to track the spread of the most resistant and virulent phylogenetic groups over time, facilitating rapid therapeutic decisions to treat infections and prevent the emergence of new resistant organisms, helping choose the most effective antibiotics and reducing treatment failure.